2018
DOI: 10.1002/hpja.182
|View full text |Cite
|
Sign up to set email alerts
|

Health and broader community benefit of parkrun—An exploratory qualitative study

Abstract: Social factors appeared critical in driving initial and ongoing parkrun participation. parkrun may lead to wider community benefits beyond that gained through increased individual PA. These findings highlight the "success factors" driving parkrun participation and provide insights for other community-based PA promotion activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…The emerging body of research on parkrun from the UK and Australia has identified the capacity of the event to engage people who are less active and experience constraints to participation: those with lower levels of education (Sharman et al, 2018), women, older people, those with various health/ mental health conditions or disabilities (Cleland et al, 2018;Grunseit et al, 2018;Morris and Scott, 2018;Stevinson and Hickson, 2014;Wiltshire, Fullagar and Stevinson, 2018). One of the first studies conducted with over 7000 parkrunners in the UK identified the majority as not having been regular runners prior to their parkrun registration and reported benefits related to psychological well-being and sense of community (Stevinson et al, 2015).…”
Section: Parkrun Research Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The emerging body of research on parkrun from the UK and Australia has identified the capacity of the event to engage people who are less active and experience constraints to participation: those with lower levels of education (Sharman et al, 2018), women, older people, those with various health/ mental health conditions or disabilities (Cleland et al, 2018;Grunseit et al, 2018;Morris and Scott, 2018;Stevinson and Hickson, 2014;Wiltshire, Fullagar and Stevinson, 2018). One of the first studies conducted with over 7000 parkrunners in the UK identified the majority as not having been regular runners prior to their parkrun registration and reported benefits related to psychological well-being and sense of community (Stevinson et al, 2015).…”
Section: Parkrun Research Literaturementioning
confidence: 99%
“…parkrun has been consistently identified as a site of social interaction that connects people in local places (Hindley, 2018) and across places with the rise of 'parkrun tourism' (Sharman et al, 2018). However, parkrun also risks entrenching inequitable patterns of access to social and cultural capital if inclusion is not addressed .…”
Section: Parkrun Research Literaturementioning
confidence: 99%
“…By extending an analysis beyond running status before registration (Cleland et al, 2019; Sharman et al, 2019; Stevinson and Hickson, 2013) and attachment to parkrun identity (Stevens et al, 2019), we have been able to make visible the timebound and embodied conditions which are a condition of changes in subjectivity within parkrun participants. Looking forward, we contend that we need to offer more long-term and stable offerings to promote physical activity which enables these identity shifts to take place.…”
Section: Discussionmentioning
confidence: 99%
“…Their work found that regular runners made up almost one-half of participants (47.2%, n =175), although here there were more occasional runners (38.2%, n =142) than walkers/non-runners (14.6%, n =54). Similarly, sporting identity before parkrun participation is addressed in the qualitative work of Sharman et al (2019), who also had non-runners as a minority within their sample. In a case study ( n =235) of one Nottingham parkrun, Hindley (2018) found that 59.1% of his participants identified as regular runners, with occasional/nonrunners (14%) and recreational/club/competitive runners (26.9%) making up the rest of the sample.…”
Section: Identity Running and Parkrunmentioning
confidence: 99%
“…We recognize parkrun’s weekly occurrence provides opportunity for regular physical activity, and parkrun participants report sense of achievement, positive atmosphere, sense of community, inclusiveness, and social opportunities as desirable traits of parkrun. 2 -5 However, these traits are also observed with other modes of physical activity. 6,7 Concerningly, Cleland and colleagues 1 did not provide a citation for their claim, and other researchers have also suggested paid-entry events are “for the privileged few.” 5 We believe such claims undermine merits of paid-entry events and perpetuate false information about parkrun.…”
mentioning
confidence: 93%